Mandibular bone height changes in two different design concepts of four implant assisted overdenture (International Journal of Scientific Research and Management (IJSRM), 2021)
Purpose: This comparative study was conducted to compare between two different design concepts of four implant assisted complete mandibular overdenture regarding the residual alveolar bone height changes. Materials and Methods: Ten healthy completely edentulous male patients were selected for this study. For each patient, a conventional complete denture was constructed. Each mandibular denture was duplicated to be used as a radiographic stent, then the CBCT surgical guide template was printed according to each design concept of 4-implant overdenture. The CBCT surgical guide templates were used for installing the implants according to flapless surgical technique followed by delayed loading. According to the two design concepts of the 4-implant overdenture used in this study, the patients were randomly classified into two equal groups: group [A]had two vertical canine implants with two axial 1st molar short implants (short design concept), and group [B]had two vertical canine implants with two distally inclined premolar implants (inclined design concept). Radiographic evaluations were performed immediately (T0), 6 months (T6), and 12 months (T12) respectively after picking up of the ball attachments.